Riau Folklore Theme Park Di Pekanbaru Dengan Penerapan Teknologi Simulator - Susilo, Bagus Ardyawan; Aldy, Pedia; Susilawaty, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Indoensia have various folk stories with any tittle and messages in the story, certainly become local wisdom in Indonesia. The story from every province in Indonesia, including in Riau province. But in nowadays, childern’s interests to folk story is decrease, folk story from abroad are very popular, for example Snow White and Cinderella. The ways can be do for take the memories interest people especially the children to Riau folk story by developt Theme Park which amusement park that tells about folk story in Riau. This theme park applying simulator technology so visitors can feel the atmosphere in the story from simulations on the amusement park. This folklore Theme Park applies the concept of